Adaptations to Emergency Remote Teaching on EFL Writing Course During the Covid-19 Pandemic - Hanna Sundari; Rr. Astri Indriana Oktavita; Nurmala Hendrawaty (Universitas Indraprasta PGRI, Jakarta, Indonesia, 2022)
Covid-19 pandemic forced lecturers and students to stay at home and manage online remote teaching systems. This current study explored the adaptations to emergency online teaching on EFL Academic Writing courses in the aspect of practices and perception from both lecturers and students at university. A mixed-method approach was selected using an exploratory sequential design. The participants were a lecturer and 51 university students who registered for the course at a private university in Jakarta. The instruments were the lecturer’s documents from 14 meetings and an online questionnaire sequentially. The data were then analyzed using descriptive as well as thematic qualitative data analysis. The findings showed that the lecturer’s adaptations consisted of digital learning platforms, material delivery, teaching methods/techniques, and writing activity and assessment. Some students assumed that attending online remote teaching was confusing, while others had no adjustments and called it a new and valuable experience. In general, they perceived positive perceptions toward teaching’s practices. WhatsApp mobile messenger with content materials in PDF format using Genre-based approach considers being very effective in managing Academic Writing courses for emergency remote teaching during the pandemic.